Analiza czynnikowa obiektów symbolicznych - Dudek, Andrzej (Factorial Analysis of Symbolic Objects, 2005)
This article presents some extensions of factorial analysis and principal component analysis onto data represented in form of symbolic object table (matrix with symbolic objects as rows). Each cell in symbolic object table can contain single quantitative value, categorical value, interval, multivalued variable, multivalued variable with weights. Vertices and Centers algorithms implementing principal component analysis on symbolic objects are described and an example of using principal component analysis on data in form of numeric intervals is presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 358-366